Legal Certainty of the Right to Severance Pay for Workers Who Retire in Companies That Undergo Acquisitions - Fajar Ramadhan; Agus Mulya Karsona; Holyness N Singadimeja (Administrative and Environmental Law Review, 2023)
The ease of transactions in the digital era has resulted in increased competitiveness between companies in the trade sector. To maintain the existence of the company, it is not uncommon for companies to restructure through the acquisition process. However, the acquisition process has an impact on the existence of workers in the previous company, especially on workers entering retirement age. Law Number 6 of 2023 on Job Creation Article 61 paragraph (3) regulates the transfer of responsibility for workers' rights which illustrates that the new employer is responsible for fulfilling workers' rights, but the transfer agreement allowed by this law does not guarantee the fulfillment of workers' rights as a whole. Therefore, it is necessary to know the legal certainty of workers entering retirement age in companies that experience acquisitions and the implementation of severance pay rights for workers entering retirement age in companies that experience acquisitions. The legal approach involves looking at secondary data or library resources. The results showed that Law Number 6 of 2023 on Job Creation concerning Interim Replacement (PHK), employees who have been laid off eligible for severance money, long service pay, and compensatory pay. The rights of workers affected by termination of employment on the grounds of entering retirement age in companies experiencing takeover are calculated based on the length of service of workers in a company, as well as the rights that have not been obtained by workers during their work which can be used as nominal money.